Electrochemical Determination of Japanese Encephalitis Virus Antigen Using Silver Nanoparticles Modified Screen-Printed Carbon Electrode - Chin, Suk Fun; Lim, Lih Shan; Lai, Huat; Pang, Suh Cem; Sia, Magdline Henry Sum; Perera, David (Host, 2019)
In this study, we aim to fabricate a silver nanoparticles (Ag NPs) based electrochemical biosensor for Japanese Encephalitis virus antigen detection. Ag NPs were deposited onto screen-printed carbon electrode (SPCE) and the electrochemical properties of the Ag NPs modified SPCE were investigated via electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). It was observed that the deposition of Ag NPs onto electrode surface has significantly enhanced the conductivity up to 20.5% than that of bare SPCE. The EIS data indicated limit of detection (LOD) of 2.60 ng/mL (at S/ N = 3) towards JEV antigen, with an analysis assay time of 20 min. This presented Ag NPs modified SPCE has demonstrated a promising and rapid alternative to conventional biosensing techniques towards JEV antigen.